Chimpanzees steal less from their friends and expect them to do the same - Oded Ritov; Christoph J. Völter; Liran Samuni; Avi Benozio; Dacher Keltner; Jan M. Engelmann; Laura S. Lewis; Esther Herrmann (Evolution and Human Behavior, 2026)

Nanoparticle Counting for PTI: The Dirty Tail Paradigm — A Pragmatic Proposal to Strongly Reduce Urban PN Pollution from Combustion Engine Fleets - A. Mayer; J. Czerwinski; Th. Lutz; F. Legerer; M. Wyser; P. Comte; L. Larsen; L. Rubino; K. Vasilatou; D. Engelmann; M. Knoll; H. Burtscher (Emission Control Science and Technology, 2025)

The role of phase transition by nucleation, condensation, and evaporation for the synthesis of silicon nanoparticles in a microwave plasma reactor — Simulation and experiment - P. Wollny; J. Menser; L. Engelmann; J. Sellmann; C. Schulz; H. Wiggers; A. Kempf; I. Wlokas (Chemical Engineering Journal, 2023)

Pro- and anti-inflammatory macrophages express a sub-type specific purinergic receptor profile - J. Merz; A. Nettesheim; S. von Garlen; P. Albrecht; B. S. Saller; J. Engelmann; L. Hertle; I. Schäfer; D. Dimanski; S. König; L. Karnbrock; K. Bulatova; et al. (Purinergic Signalling, 2021)
Extracellular nucleotides act as danger signals that orchestrate inflammation by purinergic receptor activation. The expression pattern of different purinergic receptors may correlate with a pro- or anti-inflammatory phenotype. Macrophages function as pro-inflammatory M1 macrophages (M1) or anti-inflammatory M2 macrophages (M2). The present study found that murine bone marrow-derived macrophages express a unique purinergic receptor profile during in vitro polarization. As assessed by real-time polymerase chain reaction (PCR), Gαs-coupled P1 receptors A2A and A2B are upregulated in M1 and M2 compared to M0, but A2A 15 times higher in M1. The ionotropic P2 receptor P2X 5 is selectively upregulated in M1- and M2-polarized macrophages. P2X 7 is temporarily expressed in M1 macrophages. Metabotropic P2Y receptors showed a distinct expression profile in M1 and M2-polarized macrophages: Gαq coupled P2Y 1 and P2Y 6 are exclusively upregulated in M2, whereas Gαi P2Y 13 and P2Y 14 are overexpressed in M1. This consequently leads to functional differences between M1 and M2 in response to adenosine di-phosphate stimulation (ADP): In contrast to M1, M2 showed increased cytoplasmatic calcium after ADP stimulation. In the present study we show that bone marrow-derived macrophages express a unique repertoire of purinergic receptors. We show for the first time that the repertoire of purinergic receptors is highly flexible and quickly adapts upon pro- and anti-inflammatory macrophage differentiation with functional consequences to nucleotide stimulation.

Evaluation of different samplers and storage temperature effect on the methane carbon stable isotope analysis - Victor H. J. M. dos Santos; Diane O. Laroque; Caroline I. Baum; Pâmela de M. Engelmann; Rogério V. Lourega; Luiz F. Rodrigues (Environmental Monitoring and Assessment, 2018)

Histological characterization of Passiflora pohlii Mast. root tips cryopreserved using the V-Cryo-plate technique - Mariela J. Simão; Myriam Collin; Renata O. Garcia; Elisabeth Mansur; Georgia Pacheco; Florent Engelmann (Protoplasma, 2018)

The effect of skin fatty acids on Staphylococcus aureus - Yvonne Neumann; Knut Ohlsen; Stefanie Donat; Susanne Engelmann; Harald Kusch; Dirk Albrecht; Michael Cartron; Alexander Hurd; Simon J. Foster (Archives of Microbiology, 2015)

Chronic wheel running reduces maladaptive patterns of methamphetamine intake: regulation by attenuation of methamphetamine-induced neuronal nitric oxide synthase - Alexander J. Engelmann; Mark B. Aparicio; Airee Kim; Jeffery C. Sobieraj; Clara J. Yuan; Yanabel Grant; Chitra D. Mandyam (Brain Structure and Function, 2014)

Magnetic fabric development in a highly anisotropic magnetite-bearing ductile shear zone (Seve Nappe Complex, Scandinavian Caledonides) - A. Kontny; R. Engelmann; J. C. Grimmer; R. O. Greiling; A. Hirt (International Journal of Earth Sciences, 2012)

A simple protocol for cryopreservation of zygotic embryos of ten accessions of coconut (Cocos nucifera L.) - O. N’Nan; M. Borges; J.-L. Konan Konan; V. Hocher; J.-L. Verdeil; J. Tregear; A. S. P. N’guetta; F. Engelmann; B. Malaurie (In Vitro Cellular & Developmental Biology - Plant, 2012)

Platinum anticancer agents and antidepressants: desipramine enhances platinum-based cytotoxicity in human colon cancer cells - Peyman Kabolizadeh; Brigitte J. Engelmann; Nicholas Pullen; Jennifer K. Stewart; John J. Ryan; Nicholas P. Farrell (JBIC Journal of Biological Inorganic Chemistry, 2012)

In vitro production of radiolabeled red clover (Trifolium pratense) isoflavones - Nancy J. Engelmann; Adam Reppert; Gad Yousef; Randy B. Rogers; Mary Ann Lila (Plant Cell, Tissue and Organ Culture (PCTOC), 2009)

The electric organ discharges of the Petrocephalus species (Teleostei: Mormyridae) of the Upper Volta System - T. Moritz; J. Engelmann; K. E. Linsenmair; G. Von DerEmde (Journal of Fish Biology, 2009)
In this study, a first comparative investigation of all four species of Petrocephalus ( P. bovei , P. bane , P. soudanensis and P. cf. pallidomaculatus ) present in the Upper Volta system and their electric organ discharges (EOD) was conducted. It was found that P. bovei was the most widespread (in terms of habitat use), but in several places P. bovei , P. soudanensis and P. cf. pallidomaculatus occurred syntopically. All species emitted a triphasic signal, and with very few exceptions, the Petrocephalus species of the Upper Volta system could clearly be identified on the basis of their EOD waveforms. The most obvious differences between species in EOD waveforms were in amplitude of the last phase, total duration and fast Fourier transformation (FFT) peak frequency. No sexual dimorphism was present in the EOD of any species although external dimorphism, i.e. an indentation at the base of the anal fin of mature males, was common. The EOD waveform diversity in the Upper Volta principally resembled that found in four sympatric Petrocephalus species from the Ogooué system (Gabon) and might play a role in species recognition and speciation processes.

Object localization through the lateral line system of fish: theory and experiment - Julie Goulet; Jacob Engelmann; Boris P. Chagnaud; Jan-Moritz P. Franosch; Maria D. Suttner; J. Leo van Hemmen (Journal of Comparative Physiology A, 2008)

A proteomic approach to understanding the development of multidrug-resistant Candida albicans strains - H. Kusch; K. Biswas; S. Schwanfelder; S. Engelmann; P. D. Rogers; M. Hecker; J. Morschhäuser (Molecular Genetics and Genomics, 2004)

Viral Lower Respiratory Tract Infection in the Elderly: A Prospective In-Hospital Study - J. Flamaing; I. Engelmann; E. Joosten; M. Van Ranst; J. Verhaegen; W. E. Peetermans (European Journal of Clinical Microbiology & Infectious Diseases, 2003)

Lateral line reception in still- and running water - Engelmann J.; Hanke W.; Bleckmann H. (Journal of Comparative Physiology A, 2002)

Nickel requirement in Chlorella emersonii - Carl J. Soeder; Gabriele Engelmann (Archives of Microbiology, 1984)